Analisis Losses Minyak Sawit pada Proses Pengolahan Pabrik Kelapa Sawit PT Perkebunan Nusantara IV Regional IV Unit Usaha PKS Bunut - Farhan Al rasyid Nasution; Brav Deva Bernadhi (Journal of Science, Technology, and Innovation, 2026)
This study analyzes palm oil losses during the processing stages at the Palm Oil Mill of PT Perkebunan Nusantara IV Regional IV PKS Bunut. The research aimed to identify critical loss points, evaluate causal factors, and formulate operational improvement strategies to enhance processing efficiency. The study employed an empirical industrial observation approach through direct monitoring of the Fresh Fruit Bunch processing chain, including sterilization, threshing, pressing, clarification, and kernel stations. The results indicate that several loss components, particularly press cake and solid decanter losses, exceeded industrial standard limits, reflecting process inefficiencies in specific operational units. The dominant factors contributing to losses were unstable sterilization conditions, declining screw press and decanter performance, inconsistent operational control, and variability in raw material quality. The implementation of preventive maintenance, process standardization, Statistical Process Control, and Six Sigma-based monitoring is considered capable of reducing oil losses and strengthening sustainable operational efficiency in the palm oil processing industry.